My Neighbour’s God: Interfaith Spaces and Claims of Religious Identity - Kunz-Lübcke, Andreas (Studien zur interkulturellen Geschichte des Christentums Etudes d'histoire interculturelle du christianisme / Studies in the Intercultural History of Christianity, 2019)
In the latest discussion on the relations between religions, it has often been argued that monotheism necessarily leads to intolerance and exclusivism. A religion which claims to worship «the one and only true God» is inevitably forced to reject every religious behaviour and practices of «the Other». But is this really the case? This volume contains contributions which discuss the major question: What are the instruments and the strategies used in different religious settings where interreligious encounter is part of daily life? Most of the contributions concentrate on the challenges of theology in the context of India. A special focus will be on approaches for interreligious coexistence derived from Biblical or Systematic Theology